LEARNING ACHIEVEMENT IN STEM SUBJECT: COMMONALITIES AND DIFFERENCES IN LATVIA AND FINLAND A COMPARATIVE STUDY - Galpotthawela, Nihals; Lubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Education is a never ending learning process. Learning achievement in STEM is the academic disciplines of science technology engineering and mathematics. This article reports a study on the impact of learning achievement in STEM subject in Latvia and Finland. This report bring collection of knowledge and information from other writers and OECD. Learning achievement is the result of an activity that has been done, created both individually and in groups- education. Active learning increases student performance in STEM subjects (Science, Technologies, Engineering, and Mathematics). The basic qualification for school teachers in Finland is the master´s degree and in Latvia the basic or minimum qualification for teaching needed to have at least bachelors’ degree and teaching certificate. Research evidence shows that performance in Latvia was slightly below the OECD average in STEM subjects. The impact of socio-economic factors as student’s performance must be taken into account with comparative studies both in Finland and Latvia, and how Latvia and Finlandachieve their expected goals?The theoretical study is trying to investigate the reasons of differences in learning achievement in Latvian and Finnish schools; also what influences learners success and achievement in mathematics and science. It is important from a pedagogical point of view to provide student with relevant practical and theoretical information and to promote their knowledge.